Värderingar, reglering och växelverkan på arbetsmarknaden: En kvalitativ undersökning om användningen av registerkontroller inom den privatiserade tillverkningsindustrin - Hegborn Joksimovic,Sara; Wilund,Isa (2025)
Recently, there has been a noticeable increase in Swedish media coverage concerning criminal record checks. Trade union organizations in many sectors express concern about the growing application of such background checks during recruitment processes. Various actors, from individuals in the labor market to state institutions such as the Swedish Prison and Probation Service and the Public Employment Service, have highlighted potential risks for job seekers in society. This study seeks to amplify the voices that often remain in the background of this discussion and whose perspectives form part of a much broader context - namely, those of companies. Through qualitative interviews with eight representatives from six private manufacturing companies, this study aims to shed light on thoughts, experiences, and reasoning regarding the use of criminal record checks in recruitment. The thematic analysis of the data identified areas related to regulation, personal impact, organization, society, and ethics. These subjects consequently formed the foundation for a discussion linking participants' perspectives with theoretical frameworks and current developments. The study demonstrates how organizational structures and internal regulations can influence the use of criminal record checks. It also provides awareness of ethical factors influencing individuals and organizations in their recruitment processes, along with reasoning regarding the balancing of interests.
Keywords: criminal record checks; recruitment; labour market; behavioral ethics; CSR; institutional theory; regulation